Śrītarkasaṅgrahasāra : mūḷasaha - Annambhaṭṭa, 17th cent (SAMP early 20th-century Indian books project ;, 1914)
Translation, with text in Sanskrit, of a compendium on the basic concepts and terminology of the Nyaya and Vaisesika school in Hindu philosophy.